2017
DOI: 10.5152/tud.2016.08941
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase- associated lipocalin as a screening test in prostate cancer

Abstract: Objective: Prostate specific antigen (PSA) with digital rectal examination is used for diagnosis of prostate cancer (PCa), where definite diagnosis can only be made by prostate biopsy. Recently neutrophil gelatinaseassociated lipocalin (NGAL), a lipocalin family member glycoprotein, come into prominence as a cancer biomarker. This study is aimed to test serum NGAL as a diagnostic biomarker for PCa and discriminate PCa from benign prostatic hyperplasia (BPH). Material and methods:In this prospective study, 90 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In particular, for PCa, its overexpression increased migration and invasion 31,32 ; whereas attenuation of its expression in the PCa cells decreased these processes 33,34 . Lipocalin‐2 was even considered as a screening test for PCa 35 . Microseminoprotein‐β (MSMB)/Prostate secretory protein of 94 amino acids (PSP94), primarily found in the prostatic secretion, was originally isolated and purified from human seminal plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for PCa, its overexpression increased migration and invasion 31,32 ; whereas attenuation of its expression in the PCa cells decreased these processes 33,34 . Lipocalin‐2 was even considered as a screening test for PCa 35 . Microseminoprotein‐β (MSMB)/Prostate secretory protein of 94 amino acids (PSP94), primarily found in the prostatic secretion, was originally isolated and purified from human seminal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Lipocalin-2 was even considered as a screening test for PCa. 35 Microseminoprotein-β (MSMB)/Prostate secretory protein of 94 amino acids (PSP94), primarily found in the prostatic secretion, was originally isolated and purified from human seminal plasma. Recent studies have suggested that loss of its expression was associated with PCa aggressiveness.…”
Section: Validation Of Differential Expression Of Selected Genes Anmentioning
confidence: 99%
“…Interestingly, the expression of both LNC2 and MMP9 genes was increased in 16 tumor types, demonstrating their involvement in tumor development. This result was consistent with those reported in the literature for several tumors, including BLCA ( Ricci et al, 2015 ; Candido et al, 2016b ), CESC ( Li et al, 2012 ), CHOL ( Leelawat et al, 2011 ; Nair et al, 2018 ; Li et al, 2019 ), ESCA ( Zhang et al, 2007 ), HNSC ( Ruokolainen et al, 2005 ; Hiromoto et al, 2011 ; Stanciu et al, 2016 ; Verma et al, 2017 ), KIRP ( Cho et al, 2003 ; Zhang et al, 2015 ), LIHC ( Chen et al, 2012 ; Abdelsameea et al, 2020 ), LUAD ( Ruiz-Morales et al, 2015 ), OV ( Cho and Kim, 2009 ; Gupta et al, 2022 ); PAAD ( Kaur et al, 2013 ), STAD ( Du et al, 2011 ), UCEC ( Cymbaluk-Płoska et al, 2017 ), COAD ( Yang et al, 2014 ; Ozemir et al, 2016 ; Liang and Chang, 2018 ), LUSC ( Lee et al, 2015 ), PRAD ( Ma et al, 2017 ; Muşlu et al, 2017 ; Ulusoy et al, 2021 ), READ ( Zhang et al, 2009 ; Annaházi et al, 2016 ), and THCA ( Barresi et al, 2012 ; Liu et al, 2019 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that LCN2 is secreted makes it particularly suitable as a potential non-invasive biomarker. Indeed, LCN2 has been detected in urine and serum of PCa patients [ 16 , 20 , 21 , 22 , 23 , 24 ]. Nevertheless, the underlying cellular and molecular mechanisms on how LCN2 affects PCa tumorigenesis are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%